Effect of oil palm shell carbon–polyester resin composite on microwave absorber properties - Ani, Farid Nasir; Wan Ali, Wan Khairuddin; Yusof, Ahmad Anas (Universiti Teknologi Malaysia, Faculty of Mechanical Engineering, 2005)
Pyrolysis effect on the dielectric properties of microwave absorber composed of palm shell carbon-polyester resin composite was studied. The permittivity, 0, and loss tangent, tan G of the composite were studied in the 8 to 12 GHz frequency range which emphasize the influence of carbon concentration (mass %) of pyrolysed oil palm shell carbon at 600oC, 700oC and 800oC. It was observed that the increase of carbon concentration inside each measured composite influenced the increase of 0 and tan G condition. This indicates the possibility of using carbon derived from oil palm shell residue in providing significant loss in contributing to microwave absorption, as well as an alternative in managing the increase of oil palm shell residues throughout the country.